2016
DOI: 10.1111/zoj.12409
|View full text |Cite
|
Sign up to set email alerts
|

Experimental taxonomy confirms the environmental stability of morphometric traits in a taxonomically challenging group of microinvertebrates

Abstract: Despite advances in molecular systematics, the taxonomy of tardigrades still depends largely on morphological and morphometric traits. The fact that the variability of any biological trait is determined by the interaction between genetics and environment prompts a very fundamental question: is it possible for tardigrades of the same genotype, but originating from various habitats that differ in environmental conditions, to have phenotypes so different that they would be erroneously classified as different spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 24 publications
2
59
0
1
Order By: Relevance
“…Thus, it is not certain whether the analyzed populations comprised a single or multiple (cryptic) species, which strongly restricts taxonomic conclusions which can be drawn from such studies. More recent publications, that used genetically verified identifications to investigate phenotypic variability, utilised clonal strains (Kosztyła et al., ; Stec, Gąsiorek, et al., ). Therefore, the analyzed morphological and morphometric variation was limited to phenotypic plasticity induced by environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is not certain whether the analyzed populations comprised a single or multiple (cryptic) species, which strongly restricts taxonomic conclusions which can be drawn from such studies. More recent publications, that used genetically verified identifications to investigate phenotypic variability, utilised clonal strains (Kosztyła et al., ; Stec, Gąsiorek, et al., ). Therefore, the analyzed morphological and morphometric variation was limited to phenotypic plasticity induced by environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…In a faunistic survey, Węglarska (1959) described a population of P. recamieri from Southern Poland, in which some specimens had a septulum, whereas others a microplacoid. However, according to current knowledge on the morphological variability in eutardigrades, traits such as microplacoids and septulae are constant within species (e.g., Pilato 1975Pilato , 1981Kosztyła et al 2016). Therefore, either Węglarska (1959) found two similar Pilatobius species in one locality (but see also below) or her observation was erroneous.…”
Section: Discussionmentioning
confidence: 97%
“…This is especially important in the face of the impact of climate change on Arctic biota and to understand the biogeographical patterns of life affected by these shifts, as some studies suggest that species alter their distributions rather than evolve in response to environmental changes influenced by global warming (Callaghan et al 2004;Hodkinson 2013). However, tardigrade taxonomy is based largely on morphological and morphometric traits (e.g., see Michalczyk and Kaczmarek 2013;Kosztyła et al 2016), and many species descriptions are incomplete and grossly outdated, with molecular data being available for only a small fraction of species (e.g., see Bertolani et al 2014). One such species with a poor diagnosis is Pilatobius recamieri (Richters, 1911), a limnoterrestrial eutardigrade described from and frequently found in the Svalbard Archipelago (Richters 1911;Zawierucha et al 2016a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Cryoconite granules are a consortium of archaea, cyanobacteria, heterotrophic bacteria, algae and fungi (Takeuchi et al 2001a(Takeuchi et al , b, 2010Langford et al 2014). In laboratory cultures tardigrades belonging to Hypsibioidea (e.g., genus Pilatobius) feed mainly on algae (e.g., Altiero and Rebecchi 2001;Kosztyła et al 2016). Thus, those granules may be an abundant and stable source of food for invertebrates.…”
Section: Discussion Tardigrade and Rotifer Distribution And Densitiesmentioning
confidence: 99%
“…Among the many studies on cryoconite holes in Greenland (Cook et al 2016;Hodson et al 2010a;Stibal et al 2010) few describe cyanobacteria and algae assemblages (Uetake et al 2010(Uetake et al , 2016Kaczmarek et al 2016). The Klebsormidium genus has been often recorded in extreme Arctic habitats and has a high tolerance to gradients of light, temperature and UVR (Kitzing and Karsten 2015).…”
Section: Cyanobacteria and Algae In Cryoconite Holesmentioning
confidence: 99%